Hypothesized Mechanisms Through Which Exercise May Attenuate Memory Interference - Lindsay K. Crawford; Hong Li; Liye Zou; Gao-Xia Wei; Paul D. Loprinzi (Medicina, 2020)
In this paper we introduce a mechanistic model through which exercise may enhance episodic memory, specifically via attenuating proactive and retroactive memory interference. We discuss the various types of memory, different stages of memory function, review the mechanisms behind forgetting, and the mechanistic role of exercise in facilitating pattern separation (to attenuate memory interference).